Bifunctional nanoprobe for simultaneous detection of intracellular reactive oxygen species and temperature in single cells - Yanmei Ma; Weikang Hu; Jian Hu; Muyang Ruan; Jie Hu; Ming Yang; Yi Zhang; Hanhan Xie; Chengzhi Hu (Microsystems & Nanoengineering)
Abstract Living cells can rapidly adjust their metabolic activities in response to external stimuli, leading to fluctuations in intracellular temperature and reactive oxygen species (ROS) levels. Monitoring these parameters is essential for understanding cellular metabolism, particularly during dynamic biological processes. In this study, we present a bifunctional nanoprobe capable of simultaneous measurement of ROS levels and temperature within single cells. The nanoprobe features two individually addressable nanoelectrodes, with platinum (Pt) and nickel (Ni) coatings on both sides. At the tip, these two metal layers form a nano-thermocouple, enabling precise intracellular temperature measurements, while the Pt layer facilitates selective ROS detection. This dual functionality allows for real-time monitoring of cellular responses during synergistic chemo-photothermal therapy of cancer cells and zebrafish embryos subjected to mitochondrial toxic stress. Our results demonstrate that the nanoprobe effectively measures increases in temperature and ROS levels in HeLa cells undergoing chemo-photothermal therapy, as well as in chemically stimulated zebrafish embryos. By providing detailed analysis of submicrometer-scale temperature and ROS variations within living cells, this nanoprobe offers valuable insights into cellular processes and holds promise for early disease detection and drug development.